Subclinical Epstein–Barr Virus Viremia Among Adult Renal Transplant Recipients: Incidence and Consequences. Issue 3 (17th January 2013) - Bamoulid, J.; Courivaud, C.; Coaquette, A.; Chalopin, J.‐M.; Gaiffe, E.; Saas, P.; Ducloux, D.
<x xml:space="preserve">Abstract</x> The natural history and clinical significance of posttransplant Epstein‐Barr virus (EBV) infection remain largely unknown. The aims of this study are to describe the incidence, risk factors and consequences of EBV infection after kidney transplantation. A total of 383 consecutive patients having received a kidney transplant between January 2002 and December 2010 were included. EBV polymerase chain reaction (PCR) was performed every 2 weeks for 3 months, and every 4 weeks for the next 9 months. A total of 155 of the 383 patients (40%) had at least one positive viremia during the first year posttransplant. The median time to viremia was day 31 posttransplant (14–329). A total of 73 (47%) had EBV viremia > 103 log and 23 (15%) had positive viremia for more than 6 months. EBV D+/R− patients (12/18 (67%) versus 143/365 (39%), p = 0.02) and those having received antithymocyte globulins (ATG) (54% vs. 35%; p<0.001) were more likely to develop EBV infection. EBV infection (hazard ratio [HR], 3.03; 95% confidence interval [CI], 1.72–8.29; p = 0.01) was associated with the occurrence of opportunistic infections. A positive EBV PCR during the first 6 months posttransplant was associated with graft loss (HR, 3.04; 95% CI, 1.36–6.79; p = 0.014). EBV reactivation is frequent after transplantation and reflects overimmunosuppression. Prospective studies should examine the association between EBV and graft loss.